Hukum Keluarga Berencana (KB) Menurut Agama Islam Dalam Perspektif Masyarakat Di Kota Metro - Fata Ihzamahendra; Mahfud (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This research was motivated by differing public views on the use of contraception in Islam. Some oppose it on the grounds that it contradicts the principles of Sharia law, whilst some scholars view it positively if practiced with the intention of safeguarding the health and welfare of the family. The study aims to examine the perspective of Islamic law on the use of family planning, as well as on health, education, and family welfare, particularly as an effort to safeguard maternal health in Indonesia. The sampling technique used in the research analysis is purposive sampling. The instrument used in this study was data collected using a checklist to determine the Islamic legal ruling on family planning in Metro City. The aim was to identify the types of contraceptives used, as well as the Islamic legal perspective regarding their application. Some scholars state that the use of temporary contraception is permitted, provided it does not absolutely reject the blessing of offspring. Conversely, permanent methods such as vasectomy and tubectomy are prohibited unless there are medical reasons. In conclusion, Islam allows for family planning practices under certain conditions, whilst promoting family well-being and reproductive health without violating the principles of Islamic Sharia.